KARAKTERISTIK KIMIA DAN ORGANOLEPTIK TEPUNG SORGUM VARIETAS BIOGUMA PADA PEMBUATAN BERAS ANALOG DENGAN PENAMBAHAN TEPUNG MOCAF DAN TALAS - Rahmawati, Nuri; Widata, Sri; Purwaningsih, Heni (Universitas Sarjanawiyata Tamansiswa, 2024)
Efforts to reduce the dependence on rice consumption among the Indonesian population are being made by developing alternative food sources, such as analog rice, which resembles rice but is not purely made from rice. Sorghum is highly suitable for development as a functional food because it contains complex carbohydrates that are digested more slowly, potentially reducing the glycemic response. The research site is located at the Universitas Sarjana Tamansiswa Integrated Laboratory. The research period runs from October to November 2023. The study includes the production of sorghum flour, the creation of analog rice, chemical testing of the sorghum flour, and organoleptic testing of the analog rice. fixed experimental design used in this study is a Completely Randomized Design (CRD) with one factor. fixed chemical analysis results of Bioguma sorghum flour show that it contains 65.73% starch, 6.83% protein, 4.327% fat, 2.144% ash, and 7.672% moisture. fixed analysis of variance results shows that the F1 treatment of analog rice is the most preferred by the panelists. Similar treatments using a 60% sorghum flour formulation resulted in the best treatment concentration. The best substitution for mocaf flour and taro flour is with a concentration of 13.75% mocaf flour and 13.75% taro flour. There are significant differences between the formulations of sorghum flour, mocaf flour, and taro flour in terms of taste, color, aroma, and preference parameters. However, no significant differences were found in the texture parameter.